2012
DOI: 10.1016/j.jtcvs.2012.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of pulmonary artery with porcine small intestinal submucosa in a lamb surgical model: Viability and growth potential

Abstract: Our data confirmed that remodeling and growth potential of the small intestine submucosal biomaterial are time dependent. Additional experiments are required to investigate the stability of the patch material over a longer period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In previous studies, SIS was used as a replacement for large diameter vena cava grafts in pigs [24] and as vascular patches supporting host cell infiltration [25, 26], but its performance as a small diameter arterial replacement graft has been inadequate [27], possibly due to lack of a functional endothelium. Our study showed that unlike vascular grafts based on decellularized arteries [7] or decellularized polymer based TEVs [5, 6], the endothelialized SIS-Fibrin scaffold yielded high patency rates (100%) and enabled significant repopulation by incoming host cells throughout the graft, even in the absence of donor SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, SIS was used as a replacement for large diameter vena cava grafts in pigs [24] and as vascular patches supporting host cell infiltration [25, 26], but its performance as a small diameter arterial replacement graft has been inadequate [27], possibly due to lack of a functional endothelium. Our study showed that unlike vascular grafts based on decellularized arteries [7] or decellularized polymer based TEVs [5, 6], the endothelialized SIS-Fibrin scaffold yielded high patency rates (100%) and enabled significant repopulation by incoming host cells throughout the graft, even in the absence of donor SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully introduced in surgery as a new substitute material for different applications in order to provide biocompatibility and potential remodeling or even tissue regeneration . The tissue remodeling and regeneration of this material has been demonstrated in preclinical experiments . Histological examination of explanted SIS‐ECM patches used in humans showed resorption and no calcification of the material as well as replacement with organized collagen, neovascularization, and reendothelization.…”
Section: Characteristics (Advantages and Disadvantages) Of Different mentioning
confidence: 88%
“…3 The tissue remodeling and regeneration of this material has been demonstrated in preclinical experiments. [6][7][8][9][10] Histological examination of explanted SIS-ECM patches used in humans showed resorption and no calcification of the material as well as replacement with organized collagen, neovascularization, and reendothelization. Table 2 shows the list of currently available SIS-ECM-derived products on the market with their clinical application.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Follow-on studies in the early 1990s utilized similar models to examine porcine (xenogeneic) SIS [9,10]. Over the last decade, porcine SIS and the newer SIS-ECM have been used in a variety of cardiovascular applications in a number of different animals, including pigs [8,11,21,23], sheep [12][13][14]24] and cows [22], and for a variety of purposes such as arterial or venous grafting [9][10][11][14][15][16][17], valve replacement [12,21,[23][24][25][26] and myocardial repair or patching [8,22]. Although the number of animals used in these studies was often small, these were important studies that together laid the ground for the clinical studies using SIS-ECM.…”
Section: Preclinical Studies Of Porcine Small Intestinal Submucosa Anmentioning
confidence: 99%